KERAGAAN USAHA PENANGKAR BENIH PADI CV KARYA MUKTI DI DESA GUNUNG JAYA, KECAMATAN CISAAT, KABUPATEN SUKABUMI - Rizal; Endang Tri Astutiningsih; Ema Hilma Meilani (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
Business performance is the situation or state of a business related to performance, development, and results that have been achieved. CV Karya Mukti is a seed producing center that plays a role in providing quality superior seeds for farmers in Cisaat District. This study aims to identify the business performance of CV Karya Mukti rice seed breeder located in Gunungjaya Village, Cisaat Sub-district, Sukabumi District. This study was conducted from September 2024 to January 2025 using the case study method. Business performance in this study was analyzed by calculating production costs, revenue and income. The data used in this study consisted of primary and secondary data. The results of the study show that this farm has a fairly high productivity which produces superior seeds as much as 3,900 Kg/Ha. The current selling price of superior seeds is Rp.13,000/Kg, the total income obtained by CV Karya Mukti is Rp.30,671,250/Ha/MT. This proves that the rice seed breeding business of CV Karya Mukti is very profitable, because it gets a very large income compared to the costs it incurs. Thus, the rice seed breeding business of CV Karya Mukti has bright prospects in supporting the availability of superior seeds for farmers. Keywords: Production Process, Cost, Revenue, and Income.